Prešeren, historizem in argumentacija - Sajovic, Tomaž (Jezik in slovstvo, 1997)
The starting point of the article is some important characteristics of the sonnet: the bipartite structure of form and content, argumentation and justification of the poet's insight, and the revival of the sonnet in late 18th and 19th century - the period marked by historism as a spiritual and art phenomenon. Using exaples from the Slovene narrative prose of the second half of the 19th century, Prešeren's sonnets and premises of literary, history, linguistic methods of analysis are applied in an attempt to show that in historism the three features comes together and that the mixture begins to dissolve only in the pre-modernist (Kersnik, Tavčar) and modernist period.
Keywords: historizem; Prešeren, France, 1800-1849; Slovene literature; slovenska književnost; slovenska poezija; slovenska proza; realizem; moderna; Moderna Therapeutics; argumentacija; soneti; 19. st.